Społeczno-ekonomiczne przesłanki gospodarowania zasobami nieodnawialnymi - Kulpa, Franciszek (Wydział Prawa i Administracji UAM, 1979)
A number of people involved in investigations into problems of the resources of non-renewable raw materials assume as a starting point of their reasoning the so called theory of resource scarcity. According to it the equilibrium between the disposable resources and growing needs will be destroyed in the future what will lead in consequence to a collapse of the world development. The theory of resource scarcity is based on a static concept of resources. An alternative, in relation to this theory, concept of solving the problem of equilibrium between resources of non-renewable raw materials and the demand for them is the theory of so called closed cycle. The author ends his remarks concerning general theory of managing mineral raw materials, based on the concept of "closed cycle", with the conclusion that this is the only acceptable proposal in searching for solution of the problem of non-renewable resources scarcity, since on the one hand it provides an answer to the question in which way limited resources can satisfy the man's needs over unlimited time, and on the other hand it is in conformity with basic physical laws of the nature. The concept of stabilizing human needs presented generally in the article assumes neither "forcing" stabilization by a threat of the exhaustion of the raw materials resources, nor economic stagnation. On the contrary, according to the concept, future economic development will not be slower than until now, yet it will change significantly its character from quantitative into qualitative. The stabilization of quantitative growth will be a result of natural laws that rule development. By emphasizing this question the author does not intend to say we can feel exempted from implementing into practice social (in the form of behaviour patterns) and economic (manipulating with prices of raw materials) stimuli which would induce satisfying needs by means of minimum non-renewable raw materials. The stabilization of the demand for raw materials required for manufacture of various goods should occur as a consequence of the stabilization of the number of the world population and of the total quantity of goods per capita. The process is there meant obviously of moving towards such a stabilization rather that a definite moment at which the stabilization may occur. It is widely known that the process cannot develop simultaneously either with trspeut to all countries (owing to their uneven economic advancement) or with regard to particular raw materials (stabilization levels will be spread differently over time).
Contribution to the Discussion on Socio-Economic Problems of Managing Non-Renewable Resources